PENGARUH RETURN ON EQUITY DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PT MAYORA INDAH TBK PERIODE 2013-2023 - Trias Angkasita, Karina; Nugroho Warasto, Hestu (Journal of Research and Publication Innovation, 2024)
This research aims to find out the impact of Return On Equity and Net Profit Margin on the price of the stock in Mayora Indah Tbk period 2013-2023. The independent variables in this study are Return On Equity and Net Profit Margin while the dependent variables used are Stock Price. Research methods used are quantitative descriptive methods with associative approaches. The population of this research uses data, namely financial statements with samples such as balance sheet and loss report and share price report for 11 years. (2013-2023). Data analysis techniques used are statistical descriptive analysis, classical assumption tests, double linear regression tests, and test hypotheses (t and f tests), correlation coefficient tests and test determination. The results of this study show that Return On Equity has a partially negative and significant influence on the price of the stock, seen from the significant value of 0.05 where the value is 0.043 > 0.05 while the thiting value shows a smaller return than the table size -2.408 > 2,26216 and the net profit margin variable partially has a positive and significant effect on the share price where the significant amount is smaller than 0.05, which is 0.023 < 0.05 and the thitting value indicates a larger value than the ttable size is 2,818 >2,26216. While simultaneously Return On Equity and Net Profit Margin have no significant influence on the price of the stock, where significant value yield is 0,063 > 0,05 while the test results of Fcalung show smaller than the Ftableis3,976>4,46.